TINGKAT KANDUNGAN UNSUR RADIOAKTIF AIR SUNGAI AYUNG DI DENPASAR BALI - Dewa Nyoman Alit Ardana; I Wayan Budiarsa Suyasa; I Ketut Sundra (Master Program of Environmental Science, Postgraduate Program of Udayana University)
Ayung river is one of the longest rivers in Bali. The upstream of the river is in regency of Bangli, Badung, Buleleng, Tabananand downstream is located in Padang Galak beach, East Denpasar Sub-regency. As the sample of the study, the water of the river wastaken from the stream entering the city of Denpasar. The sample was taken in five different points and for each point was taken twice. Thefirst was taken at 5 p.m, and the second was at 6 a.m. This study aims at finding out the rate of radioactive content of Ayung river water inthe city of Denpasar.The water sample was analyzed in Radiometry Analysis Group of Radiation Physics and environmental research centre andNuclear Technique Development, Jalan Taman Sari 71 Bandung – 40132. The process of counting was conducted in this place in order toknow the rate of the element activities and then identification of elements contens in the sample. The result of the counting and identifyingwas compered with standard grade of radioactivity in the area.The element of identification result and the amount of activity rate found showed that the element were natural radioactiveelements, the content: 40K (Kalium-40), 234Th (Thorium-234), 233Th (Thorium-233), 228Ac (Actinium-288), 114mIn (Indium-114m). Thehighest activity of radioactive elements in each sample point: in E2 point content element 40K with the activity 2.08 Bq/lt, in point A1 234Thwith the activity 16.34 Bq/lt, in point E1 containts 233Th with activity 598.29 Bq/lt, in point E1 and E2 contain 228Ac with the activity939.63 Bq/lt. The height of activity value of the counting and identifying elements was still under the rate of the highest level.The result of the study showed that radioactive elements 40K had the tendency of increasing radioactivity. The same thinghappened to 233Th at the peak of energi 185.00 keV. The content of its radioactive tends to exist in each point of sample point and theactivity tends to increase. Though the rate of radioactivity content was still under the highest permitted level (1x104 Bq/lt for 40K and7x102 for 233Th) bu the case needs to be watched out that the dangerus grade pollution would take place.